You must remember this - Wagner, Walter (New Yok G. P. Putnams sons, 1975)
Walter Wagner knows his Hollywood as only a thorough researcher and writer can. He has had a rare opportunity to have an inside look through the eyes of families and friends and stars alike. This singularly interesting stories illustrate he kaleidoscopic nature of my town.
Keywords: Biography